Doctor Ireneusz Jakubowski (1952–2020) - Pikulska-Radomska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Ireneusz Jakubowski combined two passions in his professional life: law and music. He was passionate about Polish history, he read a lot and knew a lot. As a lawyer, he focused on the history of Roman law as well as on the views on the law and its doctrine in Poland. As a soloist, he sang the greatest tenor parts in world music literature on many stages both in Poland and abroad.